2018
DOI: 10.1038/s41598-018-20942-9
|View full text |Cite
|
Sign up to set email alerts
|

Central Composite Design Optimization of Zinc Removal from Contaminated Soil, Using Citric Acid as Biodegradable Chelant

Abstract: Citric acid (CA) was evaluated in terms of its efficiency as a biodegradable chelating agent, in removing zinc (Zn) from heavily contaminated soil, using a soil washing process. To determine preliminary ranges of variables in the washing process, single factor experiments were carried out with different CA concentrations, pH levels and washing times. Optimization of batch washing conditions followed using a response surface methodology (RSM) based central composite design (CCD) approach. CCD predicted values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…Air sparging is commonly used for in situ soil remediation to remove volatile hydrocarbons (Mousset et al, 2014a), but there is no reported work on using it in ex situ surfactant enhanced soil washing. In addition, we optimize and validate the soil washing conditions by using response surface methodology (RSM) with central composite design (CCD), which is necessary to scale up the lab-based soil washing tests, reduce cost and improve the efficiency of contaminant removal (Asadzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Air sparging is commonly used for in situ soil remediation to remove volatile hydrocarbons (Mousset et al, 2014a), but there is no reported work on using it in ex situ surfactant enhanced soil washing. In addition, we optimize and validate the soil washing conditions by using response surface methodology (RSM) with central composite design (CCD), which is necessary to scale up the lab-based soil washing tests, reduce cost and improve the efficiency of contaminant removal (Asadzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Optimum conditions play a key role in adsorption process, especially in scaled‐up applications, in order to minimize costs and maximize pollutant removal efficiency . In classical optimization, only one factor is changed at a time to measure its effect; hence, it is time‐consuming, requires many experiments and practically fails to detect the interaction effects between individual components . Response surface methodology (RSM) is a statistical technique utilized by researchers to assess simultaneously the effects of different independent factors and to attain the most suitable operating parameters for use in the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…The chelators ISA, GLDA, PASP, and GCA are biodegradable and are not toxic or are poorly toxic (Pinto et al, 2014;Jani and Hogland, 2018), but this is not the case for EDTA (Asadzadeh et al, 2018;Golmaei et al, 2018). Consequently, the formation of metalechelator complex residues in washed soils and the transformation of metals into more unstable forms could cause plants to take up metals more easily.…”
Section: Soilsmentioning
confidence: 99%
“…Soil washing with chelators (Beiyuan et al, 2018;Lestan, 2017), among the remediation techniques, is one of the few available treatments for permanently removing metals from polluted soil that has recently been highly recommended as a feasible strategy. The simplicity of this technology, its short operation time and high efficiency, make it a practical option for PTEs removal (Asadzadeh et al, 2018;Tang et al, 2017). Selecting a suitable chelator is critical to the efficiency of the washing process (Asadzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation